The relationship between attachment and career maturity: The mediating role of self-efficacy. (January 2015) - Lee, Soon-A; Lee, Hae-Suk; Song, Haeng-Sook; Kim, Soon-Gyu
This article proposes to examine the relationship between parents, friends and teacher attachment and career maturity for adolescents and to review the mediating role of self-efficacy in the relationship between attachments and career maturity. The summary of the results is as follows. First, parent and friend attachments, self-efficacy and career maturity showed linear development over four years, but teacher attachment showed non-linear development. Second, the effect of parent attachment, teacher attachment and friend attachment on career maturity can clearly be seen through the mediation effect of self-efficacy rather than through any direct influence.